FACTORS AFFECTING THE FINANCIAL STATEMENTS QUALITY OF NONPROFIT ORGANIZATIONS - Joicenda Nahumury (Center for Indonesian Accounting Studies, 2025)
Research Objective: This study aims to determine the effect of the application of PSAK 45, human resource competence, internal Control, and the use of information technology on the quality of financial reports of nonprofit organizations Method: Structural Equation Modeling - Partial Least Squares (SEM-PLS) was used for data analysis with softwareWarpPLS 7.0 as the testing tool. Findings: The results of hypothesis testing indicate that human resources competence, internal Control, and the use of information technology affect the quality of financial reports of nonprofit organizations in Surabaya. Meanwhile, the application of PSAK 45 does not affect the quality of the financial statements Theoretical and Policy Implications - a deep explanation of Stewardship theory as part of Agency theory. The theory describes the situation in which managers are motivated to focus on the organization’s main objectives rather than their individual interests. Research Novelty: This study uses mosques as part of the subject of Research, which has seldom been studied in previous studies